IMPLEMENTASI KEBIJAKAN PROGRAM PENGEMBANGAN KAWASAN AGROPOLITAN - Siti Khusnul Dhoni, Mrs. (FIA UB, 2012)
Implementation of Agropolitan Area Development Program policy in Bangkalan is the one of the rural development strategies to increase the income of farmers, agricultural productivity, and investment in order to reduce the gap between urban and rural areas. The purpose of this study is to describe and analyze the implementation of Agropolitan Area Development Program policy in Bangkalan Regency, the results achieved from the implementation and the factors that support and hinder the policy implementation. The results of this study shows: (1) Implementation of the Agropolitan Area Development Program in Bangkalan Regency is still less than optimal. There has been some increases in terms of the welfare of farmers, agricultural productivity, as well as investment in public,Â but in a very small percentage, which is an average of less than one percent per year. (2) Factors supporting implementation include: implementers staff resources are in sufficient quantities and attitudes of implementers and community, especially the farmer groups as the target of program, support the running of the program. (3) Factors inhibiting the implementation include: the ability of implementers staff is unequal, communication and coordination among institution and the community are not good, insufficient funds, and implementer bureaucratic structures that are too long.